Power quality of dual two-level inverter fed open end winding induction motor - Hayder Ali Mohamed; Hanan Mikhael D. Habbi (Institute of Advanced Engineering and Science, 2020)
This paper presents the minimization of the total harmonic distortion (THD) of the current signal for open-end winding induction motor by using dual two-level inverter. In order to obtain a good value of THD, the space vector PWM has been used for switching the dual two-level inverter to improve the output voltage quality, gets a low common mode voltage, reduce the execution time, and to save the memory capacity. The proposed scheme uses two different DC voltage source with two two level inverter in order of minimizing the number of components. As well as it is an important to utilize the energy which increases the application of dual inverter in microgrids. All simulation results are obtained using Matlab/Simulink.